A planetary health perspective on the translation of climate change research into public health policy and practice: A scoping review protocol - Mulopo, Chanelle; Abimbola, Samuel Olushola; Onkoba, Nyamongo; Schmidt, Bey-Marrie (My University, 2024)
Climate Change (CC) emanating from anthropocentric human activities is a great threat to the quality of human life and well-being worldwide. The translation of CC research evidence can play a critical role in promoting the formulation of climate-sensitive policies to equip public health systems for CC-associated disaster preparedness, response, and management. This scoping review seeks to explore knowledge translation approaches for promoting, the uptake, and use of CC research evidence in public health policy and practice.
Keywords: Climate Change; Health Policy; Humans; Public Policy; Research Design; Review Literature as Topic